Multiproduct competition in vertically related industries - Shohei Yoshida (Osaka University, Institute of Social and Economic Research (ISER), 2015)
The paper investigates how competition between two multiproduct downstream firms in vertical relationships affects horizontal relationships: competitor collaboration and performance difference. When the upstream market consists of exclusive suppliers, the efficient firm may have incentive for technology transfer without any payment to its less efficient rival, which can be a credible device of the efficient firm to enlarge its more profitable product. Moreover, such technology transfer enhances both consumer surplus and social welfare. The inefficient downstream firm may earn more than the efficient firm under upstream markets with exclusive suppliers and with discriminatory monopolist.
Keywords: L14; L24; L41; 330; Multiproduct firm; Technology transfer; Vertical relationship; Competitor collaboration; Firm performance